The Corelation of Somatotype and Macronutrient intake with the Physical Fitness of PPLP Sport Game Athletes in West Sumatra - Zulfah Rahmah; Defriani Dwiyanti; Iswanelly Mourbas; Eva Yuniritha; Kasmiyetti Kasmiyetti (Jurnal Gizi, 2020)
Achievement of athlete in PPLP has not given good results, and even tends to decline. Physical fitness is an important factor in achievement. Among the factors that affect fitness are somatotype and nutrient intake. Suitable somatotype and balanced nutritional intake will support good performance. The purpose of this study was to study the relationship of somatotype and physical and macro nutrition intake in athletes. This study uses a cross-sectional design with a total sample of 37 people taken in total sampling. Somatotype were taken using the Heart Carter method, intake data with a 3x24 hour food recall method, and fitness data used the bleep test. Data were processed using SPSS to see the relationship of somatotype with fitness were analyzed by Chi-square statistical tests and correlation pearson test to see the relationship of macro nutrient intake with fitness. The results showed that most of them had ectomorph somatotype balance, the average nutrient intake was in the good category except that air was lacking (51,4%.%). Most athletes are in the fitter category with an average fitness of 52,12 mL/ kg /minute. Bivariate results showed that there was no relationship between somatotype and fitness but there was a relationship between macro-nutrient intake and fitness.